Wybrane problemy wdrażania rozwiązań wspomagających zarządzanie - Wroński, Paweł (Some problems of the practical application solutions helping the process of management, 2006)
Changes occurring in enterprises, under conditions of frequent changes in surroundings and open markets, require from managers to make decisions which are based on substantial information about business activity. This article presents results of research on using and implementing methods which are helpful in managing companies. Research was carried out in 25 enterprises in 2005. The conclusions concern for example problems of implementation of cost accounting and management accounting methods, factors limiting controllership, reengineering in management and the main direction of improvement management methods in those enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 418-426